Implementasi Good Government Sebagai Upaya Pencegahan Fraud Dalam Pengelolaan Keuangan Desa - Ira Megasyara; Amrizal Imawan (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to explore and reveal the application of the principles of good governance as an effort to prevent fraud in managing village government finances. Methodology/approach: This research is a qualitative research with an interpretive approach and to obtain the data using interviews and observations. Data collection was carried out by conducting in-depth interviews with informants who understood the research theme and could provide information and be involved in managing village finances, namely the village chief and the chairman of the village consultative body. Besides that, researchers also made observations and documentation related to evidence that supports the implementation of the principles of Good Corporate Governance (GCG) in managing village finances. Findings: The results of this study are that the village government has implemented the principles of good governance, namely community participation, budget transparency and policy programs, accountability as well as discipline and order in every stage of village financial management starting from the stages of planning and budgeting, program implementation and reporting or accountability, implementation of the principles of good governance has proven to be able to prevent acts of fraud in managing village finances. Because the community has access to oversee and supervise the village government in managing village finances. So that there is loophole to commit fraudulent acts. Practical implications: The implication of this research is that village governments must be creative and continue to improve the quality of good governance. Originality/value: Using the Good Government (GG) theory to prevent fraud in village financial management